2018
DOI: 10.1055/a-0752-0061
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Ovary Syndrome is Associated with Elevated Periostin Levels

Abstract: Purpose Periostin is a secreted extracellular matrix protein that is strongly associated with triglyceride metabolism, chronic inflammation, and insulin resistance. Growing evidence suggests that there is a link between periostin and ovarian function. Our aim was to ascertain whether circulating periostin levels are altered in women with polycystic ovary syndrome (PCOS) and to further explore the relationship between periostin and glucose metabolism disorder in PCOS patients. Methods In total, 50 women with PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
(30 reference statements)
2
10
1
Order By: Relevance
“…There is conflicting data concerning the role of periostin in lipid metabolism. By contrast with our results, in two Chinese studies involving young women with polycystic ovary syndrome [ 29 ] and adult obese patients with type 2 diabetes [ 33 ], periostin concentration was directly correlated with BMI and triglycerides and inversely correlated with HDL-cholesterol. Lu et al found that overexpression of periostin in obese rats resulted in liver steatosis and hypertriglyceridemia via activation of c-Jun N-terminal kinase (JNK) signaling pathway and downregulation of peroxisome proliferator-activated receptor alpha (PPARα) [ 60 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…There is conflicting data concerning the role of periostin in lipid metabolism. By contrast with our results, in two Chinese studies involving young women with polycystic ovary syndrome [ 29 ] and adult obese patients with type 2 diabetes [ 33 ], periostin concentration was directly correlated with BMI and triglycerides and inversely correlated with HDL-cholesterol. Lu et al found that overexpression of periostin in obese rats resulted in liver steatosis and hypertriglyceridemia via activation of c-Jun N-terminal kinase (JNK) signaling pathway and downregulation of peroxisome proliferator-activated receptor alpha (PPARα) [ 60 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Our multivariate analysis revealed a positive correlation between uric acid and periostin levels. A similar positive relation was found in Chinese adult women with polycystic ovary syndrome [ 29 ]. It is possible that periostin is released in response to subclinical damage caused by uric acid elevation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Additionally, POSTN knockdown attenuated 5/6 nephrectomy-induced intrarenal activation of the renin-angiotensin system, fibrosis, and inflammation in rats, implying a role in the development of CKD (Bian et al, 2019a). In a risk prediction model of ovarian cancer, POSTN combined with two other markers had high prognostic accuracy (Riester et al, 2014), and another study found that polycystic ovary syndrome is associated with elevated POSTN levels (Chen et al, 2019). Although POSTN levels in human urine may have prognostic value in IgAN, this has not been confirmed (Hwang et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…The role of the extracellular matrix in the development of cancer has also been demonstrated, including those associated with epithelial cells in the ovary [ 7 ]. The role of the ECM has also been described in the pathogenesis of other diseases related to the reproductive system, including PCOS (polycystic ovary syndrome) [ 8 , 9 , 10 ] and POI (premature ovarian insufficiency) [ 11 , 12 ]. The extensively described involvement of extracellular matrix components in signaling pathways within the ovary highlights the role of the ECM in folliculogenesis [ 13 ] and in pathological processes [ 14 ] which altogether may provide valuable therapeutic insights.…”
Section: Introductionmentioning
confidence: 99%